2022
DOI: 10.31083/j.fbl2708238
|View full text |Cite
|
Sign up to set email alerts
|

Endostar Synergizes with Radiotherapy to Inhibit Angiogenesis of Cervical Cancer in a Subcutaneous Xenograft Mouse Model

et al.

Abstract: Background: To investigate the synergic effect and underlying mechanism of Endostar, a recombinant human endostatin used for antiangiogenesis, in radiotherapy for cervical cancer. Methods: The Cell Counting Kit-8 (CCK-8) assay and plate cloning experiment were first employed to analyze the proliferation of HeLa and SiHa cervical cancer cells and human umbilical vein vascular endothelial cells (HUVECs). Flow cytometry was used to detect apoptosis and cell cycle progression. A tube formation assay was used to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that endostar blocked pathological angiogenesis to inhibit tumor formation and metastasis by binding with multiple targets [42]. It was found that endostar combined with radiotherapy or chemotherapy had excellent application prospects [22,43]. In this study, we evaluated the therapeutic effect of endostar in combination with cisplatin in NSCLC mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that endostar blocked pathological angiogenesis to inhibit tumor formation and metastasis by binding with multiple targets [42]. It was found that endostar combined with radiotherapy or chemotherapy had excellent application prospects [22,43]. In this study, we evaluated the therapeutic effect of endostar in combination with cisplatin in NSCLC mice.…”
Section: Discussionmentioning
confidence: 99%
“…(23) VEGF assumes a significant part in cancer angiogenesis, and lymphangiogenesis and animates the development of veins in growth tissue, expanding the conveyance of oxygen and supplements to the cancer and in this way advancing its multiplication and metastasis. (24,25)…”
Section: Serum Vegf-a Levels Before Therapy With Chemotherapy Responsementioning
confidence: 99%